Maternal Factors in Pregnancy and Ethnicity Influence Childhood Adiposity, Cardiac Structure, and Function - Khan, Sophia; Whatmore, Andrew; Perchard, Reena; Khan, Aysha; Vyas, Avni; Dua, Jaspal; Cruickshank, J. Kennedy; Clayton, Peter (Frontiers in Pediatrics, 2022)
Importance The links between maternal and offspring adiposity and metabolic status are well established. There is much less evidence for the impact of these relationships combined with ethnic background on cardiac structure and function in childhood. Objective To test the hypothesis that ethnicity, maternal adiposity and glycaemic status, and child adiposity affect cardiac structure and function. Design A prospective cohort study Setting A single centre mother-child cohort study. The cohort is a subset of the international multicentre Hyperglycaemia and Adverse Pregnancy Outcomes (HAPO) study. Participants: This study included 101 healthy prepubertal British born children (56 White European (WE) and 45 South Asian (SA)), median age of 9.1 years, range 6.0-12.2 years, at the time of investigation. Main outcomes and measures Anthropometric and echocardiographic measurements were made on the cohort. Maternal pregnancy and birth data were available. Relationships between maternal parameters (BMI and glucose status), child adiposity and echo measures were assessed. Results Despite no ethnic difference in BMI SDS at 9 years, SA children exhibited higher levels of body fat than WE children (whole body, right arm and truncal fat all p<0.001). SA children also exhibited greater changes in weight and height SDS but not BMI SDS from birth than WE children. As expected, maternal BMI correlated with child BMI (r=0.28; p=0.006), and body fat measures (e.g. whole body fat r=0.25; p=0.03). Maternal fasting glucose levels were associated with child body fat measures (range for r=0.22-0.28; range for p=0.02-0.05). Left ventricular (LV) indices were not different between SA and WE children, but E/A and E’/A’ (measures of diastolic function) were lower in SA compared to WE children. LV indices correlated positively to BMI SDS and body fat markers only in SA children. Maternal fasting and 2-hour glucose were negatively correlated with E’/A’ in SA (r=-0.53, p=0.015 and r=-0.49, p=0.023 respectively) but not WE children. Conclusion and Relevance SA and WE children exhibit differences in adiposity and diastolic function at 9 years. Novel relationships between maternal glycaemia, child adiposity and cardiac structure and function, present only in SA children, were identified.